Safety, Tolerability, and Efficacy of Pain Reduction by Gabapentin for Acute Headache and Meningismus After Aneurysmal Subarachnoid Hemorrhage: A Pilot Study - Dhakal, Laxmi P.; Turnbull, Marion T.; Jackson, Daniel A.; Edwards, Emily; Hodge, David O.; Thottempudi, Neeharika; Kamireddi, Prasuna; Akinduro, Oluwaseun O.; Miller, David A.; Meschia, James F.; Freeman, William D. (Frontiers in Neurology, 2020)
Patients with aneurysmal subarachnoid hemorrhage (aSAH) typically experience excruciating headaches. We hypothesized that gabapentin would be safe and tolerable for aSAH-induced headaches and reduce concurrent narcotic use. We performed a single-center, double-blind, randomized, placebo-controlled trial from November 24, 2014, to June 24, 2017, where aSAH patients received either dose-escalating gabapentin or oral placebo, both with a standard of care pain regimen. After 7 days, patients had the option to continue in an open-label period until 14 days after enrollment or until discharge from the intensive care unit. Our primary endpoint was the efficacy of gabapentin in reducing headache numeric pain scores and narcotic usage in patients with aSAH compared to the placebo group. We identified 63 potential patients with aSAH for the study. After applying stringent exclusion criteria, 16 eligible patients were enrolled into 1 of 2 arms. The study ended prematurely after reaching a prespecified funding period and unexpected drop in aSAH cases. There was a trend towards lower headache numeric pain scores and narcotic use in the gabapentin treated arm; however, this was not significantly different. Gabapentin was well tolerated and no adverse effects were reported. We report the first small randomized trial of gabapentin for aSAH-related headache. While there was a trend towards lower pain scores and narcotic requirements in the gabapentin group, the study was underpowered to detect a difference. Larger multicenter trials are required to evaluate the efficacy of gabapentin to reduce narcotic requirements after aSAH.